FRI0274 Pregnancy Outcomes in Women with Rheumatologic Conditions Exposed to Infliximab. (10th June 2014) - Kalari, S.; Granath, F.; Guo, C.-Y.; Harrison, D.D.; Broms, G.; Geldhof, A.; Nissinen, R.; Sanders, M.; Gissler, M.; Pedersen, L.; Sorensen, H.T.; Kieler, H.
Abstract : Background: RA, AS, and PsA are approved indications for infliximab (IFX). In the US, IFX is a pregnancy Category B drug. For RA and some PsA patients, IFX is administered with MTX, an agent with teratogenic and abortifacient properties. Objectives: To characterize pregnancy outcomes in rheumatology patients treated with IFX, data available to the manufacturer through spontaneous reporting and through a pregnancy registry are presented. Methods: Data from the Company safety database on individual, spontaneously reported pregnancies worldwide through Feb 23, 2013 were analyzed. The analysis focused on prospectively reported (ie, pregnancy outcome not known when first reported) cases of maternal IFX use for RA, AS, or PsA during pregnancy or within 2 months prior to conception and a known pregnancy outcome. In addition, data through Dec 31, 2010 from a Company-sponsored pregnancy registry study, undertaken to address health authority post-marketing commitments for IFX-exposed pregnancies, were analyzed; data were obtained from national medical registries in Sweden, Denmark and Finland. Maternal characteristics and pregnancy outcomes (births beyond 22 weeks of gestation) were analyzed among RA, AS, and PsA patients exposed to IFX or non-biologic systemic therapy during pregnancy or within 3 months prior to conception. Results: 56 prospective reports (37 RA; 12 AS; 6 PsA; 1 RA&AS) of IFX exposure during pregnancy were identified. Mean maternal age was 31 years. 76.8% resulted in a live birth. Birth defects were reported for 3 live births: intestinal malrotation (1), hypospadias (1), and cardiac/coronary artery perforation (1). Of the 56 reports, MTX use was reported in 10 (8 RA), including the hypospadias case; it is possible that additional RA patients may have been exposed to MTX during their pregnancy. 23.2% of the pregnancies resulted in an induced (7) or spontaneous abortion [SAB] (6); 4 of the latter had MTX exposure. In the registry study, 27 IFX-exposed pregnancies were identified (18 RA; 5 AS; 4 PsA). Mean maternal age was 31.2 years. Birth defect was reported in 1 of the 27 IFX-exposed infants (atrial septal defect/metatarsus varus) and in 133 of the 1, 974 infants exposed to non-biologic systemic therapy. Conclusions: Review of pregnancy outcomes after IFX exposure in utero showed that 76.8% of spontaneous, prospectively reported pregnancies with known outcomes resulted in live births. The most frequently identified congenital anomalies were cardiovascular defects, the most common birth defect in the general population. While there did not appear to be an increased rate of birth defects compared to the general population, the rates in both datasets were based on small study populations. Additionally, the use of MTX, an agent contraindicated in pregnant women, was reported in more than half of the SABs. Spontaneous reporting is limited by the lack of a direct comparison group, the variable amount of data provided, and a possible reporting bias towards more serious cases. The registry study was limited to the Nordic population and data only included births from 22 weeks of gestation onwards. Disclosure of Interest: S. Kalari Employee of: Janssen Research & Development, LLC., F. Granath Grant/research support: Janssen, C.-Y. Guo Employee of: Janssen Research & Development, LLC., D. Harrison Employee of: Janssen Research & Development, LLC., G. Broms Grant/research support: Janssen, A. Geldhof Employee of: Janssen Biologics Europe, R. Nissinen Employee of: Janssen Biologics Europe, M. Sanders Employee of: Janssen Research & Development, LLC., M. Gissler Grant/research support: Janssen, L. Pedersen Grant/research support: Janssen, H. Sorensen Grant/research support: Janssen, H. Kieler Grant/research support: Janssen DOI: 10.1136/annrheumdis-2014-eular.2038